O contexto de prática da política de inclusão na ótica dos estudantes do público-alvo da educação especial - Sebin, Bruna Raffaini (Universidade Federal de São Carlos, 2021)
The present study is part of the matrix project that aimed to carry out a multidimensional assessment from the perspective of different actors whose policies on schooling of students with special education needs (SEN) directly affect it. Bearing in mind that the National Education Plan recommends carrying out studies with the objective of monitoring as goals of educational policies, the objective of this study was to analyze a schooling policy for SEN student’s perspectives. The research anchored in the Policy Cycle Approach perspective had SEN students as actors. The design involved a multi-method research based on the analytical perspective that offers a possibility to interpret the information in a quantitative and qualitative way, for triangulation of results. The study conducted in a small municipality in the state of São Paulo involved 65 SEN students, (56 from elementary school cycle 1, and 9 from elementary school cycle 2) from seven schools in the municipal education system. The instruments used to collect data was closed questionnaires through the SurveyAnyPlace platform and saved in spreadsheets, generating the quantitative database and a semi-structured interview script carried out with five participants. For the analysis of quantitative data, item scoring criteria were created, which were grouped into 15 indicators and, and these in six categories. After converting the responses generated in the database to numerical data (based on the established criteria), we calculated arithmetic averages for each of the indicators, requirements and a general average for the municipality studied. We transcribed the reports obtained in the focus group and excerpts selected to illustrate and support the quantitative data. The aspects of Municipal School Inclusion Policy by Students well evaluated by the students were: 1. Participation (7.1-good), 3) Assessment of learning (6.6- good), 4) Relationships (7.1 - good) and 5) Self-assessment (8.2 - very good). The aspects that deserve more attention from the policy managers and teachers were: 2) Specific support and services (5.5 - regular), and 6)- Accessibility (5.6-regular). The general index for the municipality was good (6.3). We conclude that: a) the questionnaires used need improvement; b) the focus group technique with the students was challenging and the data were succinct due to the complexity of inciting and maintaining deep dialogues and; c) SEN students, even within the collection challenges, demonstrated that their perspectives are unique and their voices are fundamental in the elaboration of schooling policies. We expect that this study will contribute to the area of special education and that the voices of students will be heard and valued.
The context of inclusion policy practice from the perspective of special education target public students
Keywords: Educação especial; Escolarização do público-alvo da educação especial; Análise de política; Estudantes do público-alvo da educação especial; Special education; School inclusion; Students with special education needs; Policy analysis; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL